2013
DOI: 10.1038/ng.2677
|View full text |Cite
|
Sign up to set email alerts
|

DNase I–hypersensitive exons colocalize with promoters and distal regulatory elements

Abstract: The precise splicing of genes confers an enormous transcriptional complexity to the human genome. The majority of gene splicing occurs cotranscriptionally, permitting epigenetic modifications to affect splicing outcomes. Here we show that select exonic regions are demarcated within the three-dimensional structure of the human genome. We identify a subset of exons that exhibit DNase I hypersensitivity and are accompanied by ‘phantom’ signals in chromatin immunoprecipitation and sequencing (ChIP-seq) that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 59 publications
9
118
0
Order By: Relevance
“…Interestingly, the later set of genes contained multiple active enhancers within their gene bodies in DKO1 cells, and these same enhancers were methylated in HCT116 cells. Intronic enhancers have been previously described to regulate the genes they reside within [23,[31][32][33]. Here, we have identified several hundred genes that may be controlled by increases in active histones at intragenic enhancers.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the later set of genes contained multiple active enhancers within their gene bodies in DKO1 cells, and these same enhancers were methylated in HCT116 cells. Intronic enhancers have been previously described to regulate the genes they reside within [23,[31][32][33]. Here, we have identified several hundred genes that may be controlled by increases in active histones at intragenic enhancers.…”
Section: Discussionmentioning
confidence: 87%
“…1D). Although the function of H3K27me3 in gene bodies remains unclear, recent studies have suggested that it may be related to alternative promoter use (18), alternative splicing (19,20), or monoallelic gene expression (21). Long noncoding RNAs have recently been implicated in gene regulation and Polycomb recruitment (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…133 DNase I hypersensitive sites are also a mark of open chromatin regions containing promoters and enhancers. 134 Assay for transposase-accessible chromatin with highthroughput sequencing is a useful method for measuring chromatin accessibility genome wide. 135 An important caveat is that these analyses require genome-wide chromatin data from a relevant cell type.…”
Section: From Locus To Functionmentioning
confidence: 99%